Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sea lions as a natural model for charting the developmental course following in utero exposure to domoic acid - Peter F. Cook; Colleen Reichmuth; Megan E. Moriarty; Alissa C. Deming; Vanessa Fravel Hoard; Cara Field; Frances Gulland (Harmful Algae, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Conjoint use of hydraulic head and groundwater age data to detect hydrogeologic barriers - Sarah K. Marshall; Peter G. Cook; Leonard F. Konikow; Craig T. Simmons; Shawan Dogramaci (Hydrogeology Journal, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

PATHOGENICITY OF CHORISTONEURA FUMIFERANA NUCLEOPOLYHEDROVIRUS PROPAGATED IN VITRO AT DIFFERENT INCUBATION TEMPERATURES - PETER M. EBLING; GUIDO F. CAPUTO; BARBARA J. COOK (In Vitro Cellular & Developmental Biology - Animal, 2003)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An assessment of the use of low-level aerobic swimming in promoting recovery from handling stress in rainbow trout - Walter F. Meyer; Peter A. Cook (Aquaculture International, 1996)